Policy Brief: Strengthening Nurses’ OCB through Coworker Support, Satisfaction, and Culture at RSUD Batam - Nelli Roza; Desy; Roza Erda; Didi Yunaspi; Sumiati (Unram Journal of Community Service, 2026)
The purpose of this policy brief is to offer strategic suggestions for improving the Organisational Citizenship Behaviour (OCB) of nurses at RSUD Embung Fatimah Batam. This study's main goal is to investigate how coworker support affects OCB while taking job satisfaction and culture into account as mediating factors. 146 nurses participated in the study, which used structural equation modeling-partial least squares (SEM-PLS) as a quantitative method. The results show that OCB is greatly impacted by coworker support, both directly and indirectly through job satisfaction. Culture continues to be contextually relevant in creating a supportive work environment even when it does not exhibit a statistically significant effect. These results serve as the basis for hospital policy recommendations that aim to improve worker happiness, encourage extra-role behaviours that promote the quality of nursing services, and strengthen collegial work systems.